Performance of squilla meal incorporated diet on the juveniles of Labeo rohita(Ham.) - Rao, L M; Kumar, K Satish (Indian Journal of Fisheries, 2011)
Performance of squilla meal incorporated diet on the juveniles of Labeo rohita(Ham.)